A new species of the genus Diptilomiopus Nalepa and a key to diptilomiopid species (Prostigmata; Eriophyoidea; Diptilomiopidae) associated with Moraceae plant family - Khan, Eid Muhammad; Kamran, Muhammad; Alatawi, Fahad Jaber (Zootaxa, 2023)
The subfamily Diptilomiopinae Keifer and the genus Diptilomiopus Nalepa (Prostigmata; Eriophyoidea; Diptilomiopidae) are recorded for the first time from Saudi Arabia with the description and illustration of a new species, D. bahaensis sp. nov., collected from Ficus carica L. (Moraceae). Additionally, a key to diptilomiopid mite species reported from the plant family Moraceae is provided, along with their distribution and habitus to the host plants.